Clinical evidence in the phenomenon of Demonic Possession - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Purpose: Starting from the classic definition of "demonic possession" (as a psychophysical condition in which a person becomes the victim of a supernatural being of demonic origin), the present research, starting from the study published in 2019 on the proposed clinical classification of this particular phenomenon, is aimed at confirming the theoretical assumption of psychopathological origin, refuting the assumptions of the most significant analytical orientations, such as the ethnopsychiatric, the socio-anthropological, the cultural, the religious and the esoteric, to reaffirm the accuracy of the theoretical approach of the multifactorial model proposed in the previous research.  Methods: Clinical interview, based on narrative-anamnestic and documentary evidence and the basis of the Perrotta Human Emotions Model (PHEM) concerning their emotional and perceptual-reactive experience, and administration of the battery of psychometric tests published in international scientific journals by the author of this work: 1) Perrotta Integrative Clinical Interviews (PICI-2), to investigate functional and dysfunctional personality traits; 2) Perrotta Individual Sexual Matrix Questionnaire (PSM-Q), to investigate the individual sexual matrix; 3) Perrotta Affective Dependence Questionnaire (PAD-Q), to investigate the profiles of affective and relational dependence; 4) Perrotta Human Defense Mechanisms Questionnaire (PDM-Q), to investigate the defence mechanisms of the Ego.  Results: The preliminary results of the interviews and the anamnestic form would suggest that the phenomenon of demonic possession has a greater tendency to manifest itself in the female group, in the juvenile group (and tends to decrease but not to disappear with the advancement of age) and in the group geographically originating in the centre-south of Italy (due to greater religious influences, popular beliefs and ancestral fideistic representations). Moreover, the subsequent findings would lead to deduce with almost total certainty, concerning the selected sample, that the phenomenon of demonic possession has an absolute prevalence in the believing population, faithful or in any case trusting in the existence of paranormal phenomena per se, even in the absence of objective and/or scientific evidence. Based on the PICI-2 it emerged that the primary emerging disorder turns out to be alternatively the delusional disorder, the dissociative disorder and the obsessive disorder; followed, as secondary disorders, by the delusional disorder (if it is not considered as primary disorder), the schizoid disorder, the borderline disorder and the psychopathic disorder. Even the analysis of functional traits has reported the marked dysfunctional tendency of the classes that refer to self-control, sensitivity, Ego-ID comparison, emotionality, ego stability, security and relational functionality, reaffirming here too the marked dysfunctional tendency of the clinical population. According to the PSM-Q, more than 1/4 of participants present a lack of acceptance of their sexual orientation and a marked tendency to chronicle feelings of shame into dysfunctional sexual behaviours of avoidance or hypersexuality. Still, nine in ten reports having experienced severe psychological or physical abuse at a young age, or intraparental relational imbalance, or otherwise a sexual upbringing that was not open and lacked free communication. According to the PDM-Q, 37.2% are affected by affective dependence, with a greater emphasis on types I (neurotic), V (borderline), III (histrionic), and VII (psychotic) in that order of descent. Finally, the PDM-Q reveals the widespread psychopathological tendency of the ego function framework for the mechanisms of isolation, denial, regression, reactive formation, denial, projection, removal, withdrawal, instinct, repression, and idealization. Conclusions: The present research demonstrates beyond any reasonable doubt the psychopathological nature of the phenomenon of demonic possession, which deserves to be treated pharmacologically and with a psychotherapeutic approach (preferably cognitive-behavioural and/or strategic), according to the symptoms manifested and the severity of the morbid condition.